DISTRIBUTION OF DIFFERENT FIBER TYPES OF M-EXTENSOR CARPI RADIALIS LONGUS OF THE RAT - Rodrigues, ADC; Silva, JDP; Pai, V. D. (Blackwell Wissenschafts Verlag Gmbh, 1994)
As revealed by the NADH-diaphorase and myosine ATPase, the M. extensor carpi radialis longus of the rat possesses at least 3 main kinds of fibres, with different distribution on the superficial and deep portions of the muscle. The superficial portion revealed that 67.68 % are FG (fast-twitch-glycolytic) fibres, 14.72 % are FOG (fast-twitch-oxidative) fibres and 17.60 % are SO (slow-twitch-glycolytic) fibres. Already the deep portion revealed that 71.29 % are SO (slow-twitch-glycolytic) fibres, 17.46 % are FOG (fast-twitch-oxidative-glycolytic) fibres and 11.25 % are FG (fast-twitch-glycolytic) fibres. The miosine ATPase reaction was used to demonstrate contracting characteristics. These findings suggest that the movements of fast contraction of the M. extensor carpi radialis longus are predominant.